Política ótima de manutenção preventiva de transportadores de correia de uma empresa mineradora brasileira sob a suposição de reparo imperfeito - Cássius Henrique Xavier Oliveira (2016)
The reliability of systems has been a recurring issue in several articles. The reason for this increased focus on the issue lies in the fact that the operation and maintenance are strongly related to safety and environmental factors that inuence the level of corporate protability. In this regard, maintenance has been seen as a strategic activity and vital to the good reputation of the institutional image. However, the maintenance activity involves many costs. Therefore, it should develop methods that aim to determine the optimal frequency of preventive maintenance in order to minimize the total cost of maintenance. This is one of the main objectives of the various studies on this subject. Achieving this goal involves observing data repairable systems failure times of interest, establish the eect of proper repair in each intervention to be performed on these systems and to establish the conditions for the implementation of preventive and corrective maintenance. This paper uses the following assumptions: after each failure there will be a corrective maintenance which repair will be imperfect (ie, it will return the system to a condition that is not equivalent to a new system, but it will become better than it was at the time of failure ); at the same interval size there will be a perfect preventive maintenance to repair (which will cause the system to behave as a new system). The use of such assumptions result in the generation of maximum likelihood functions using classic literature models called ARA and ARI. The computational packages developed by Madureira (2014) and Fernandes (2015) will be used also. This study aims to establish an optimal maintenance policy for conveyor belts of a Brazilian mining company. Thus, this study provides a literature review combining conventional methods, and more recent hitherto not used together, while exemplifying their applications